The Ecranisation Of Alice In The Wonderland - Yanti Rahayuningsih; Arlisa Indriawati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The ecranisation is a process of filtering, transferring, or eliminating features from a novel into a film. The purpose of this study is to explore different adaptations of Lewis Caroll's (1832-1898) classic books Alice's Adventures in Wonderland and Alice in Wonderland’s Tim Burton (2010). It is necessary to understand how adaptation theory used to transform a literary work into the visual structure of a film. This study also shows how different forms of media presentation can influence adaptation differently.